2009
DOI: 10.14430/arctic32
|View full text |Cite
|
Sign up to set email alerts
|

Point Counts Underestimate the Importance of Arctic Foxes as Avian Nest Predators: Evidence from Remote Video Cameras in Arctic Alaskan Oil Fields

Abstract: ABSTRACT. We used video cameras to identify nest predators at active shorebird and passerine nests and conducted point count surveys separately to determine species richness and detection frequency of potential nest predators in the Prudhoe Bay region of Alaska. From the surveys, we identified 16 potential nest predators, with glaucous gulls (Larus hyperboreus) and parasitic jaegers (Stercorarius parasiticus) making up more than 80% of the observations. From the video evidence, however, we identified arctic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 39 publications
5
61
0
Order By: Relevance
“…Point counts were separated by at least 200 m and conducted at least 10 minutes apart. We counted all visual and aural detections of documented or suspected potential nest predators (Poole et al, 2003;Liebezeit and Zack, 2008) within an area 300 m beyond the plot boundary. We avoided re-counting individual predators by noting differences in plumage (e.g., light morph versus dark morph jaegers) and pelage (arctic fox) and by tracking active predator nests and fox den activity on or near study plots.…”
Section: Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Point counts were separated by at least 200 m and conducted at least 10 minutes apart. We counted all visual and aural detections of documented or suspected potential nest predators (Poole et al, 2003;Liebezeit and Zack, 2008) within an area 300 m beyond the plot boundary. We avoided re-counting individual predators by noting differences in plumage (e.g., light morph versus dark morph jaegers) and pelage (arctic fox) and by tracking active predator nests and fox den activity on or near study plots.…”
Section: Field Methodsmentioning
confidence: 99%
“…While we cannot say with certainty that this finding is related to negative impacts from oilfield development, it does agree with findings from Liebezeit et al (2009) that documented lower longspur survivorship closer to oilfield infrastructure. In addition, at least one potential nest predator, the glaucous gull, was more numerous at Prudhoe Bay, although most evidence suggests that the arctic fox was the more important predator at this site (Liebezeit and Zack, 2008). Lemming abundance was included as a variable in the top models, with years of higher lemming numbers corresponding to lower predation rates.…”
mentioning
confidence: 99%
“…despite these greater numbers, nest-survival rates were generally high both in and outside the landfill throughout our study. perhaps this should not have been surprising because other studies in the Arctic have found Glaucous Gulls to have little effect on survival of shorebird nests (Smith et al 2007, Liebezeit andZack 2008). The small effect Glaucous Gulls have on nests was also apparent in a study of the species' diet in the barrow area from 2007 to 2009: only 4% of all samples of the Glaucous Gull's diet contained avian eggs (E. L. Weiser, pers.…”
Section: Discussionmentioning
confidence: 89%
“…We also have other circumstantial evidence that supports the notion that greater nest survival was due to the exclusion of foxes from the landfill. first, foxes are rarely observed during predator surveys but often depredate large numbers of arctic shorebird nests (Liebezeit and Zack 2008). Second, there is a direct correspondence between the lower nest-success rates outside the landfill in 2009 and a change to less effective trapping methods for the arctic fox in that year (Savory et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because predator point counts can underestimate the importance of mammalian predators (Liebezeit and Zack 2008), we used data from an arctic fox (Vulpes lagopus) removal program conducted to enhance Steller's Eider (Polysticta stelleri) productivity (see Gilsdorf and Rossi 2008, Savory et al 2009, Bair et al 2011) as an index of mammalian predator levels. Between 2005 and 2012, trappers removed adults and kits at dens and opportunistically shot and trapped adult foxes from mid-late-May to mid-July across~220 km 2 that included the greater Barrow area and our study plots.…”
Section: Data Collectionmentioning
confidence: 99%